Low intensity 635 nm diode laser irradiation inhibits fibroblast–myofibroblast transition reducing TRPC1 channel expression/activity: New perspectives for tissue fibrosis treatment. Issue 3 (10th December 2015) - Sassoli, Chiara; Chellini, Flaminia; Squecco, Roberta; Tani, Alessia; Idrizaj, Eglantina; Nosi, Daniele; Giannelli, Marco; Zecchi‐Orlandini, Sandra
Abstract : BACKGROUND AND OBJECTIVE: Low‐level laser therapy (LLLT) or photobiomodulation therapy is emerging as a promising new therapeutic option for fibrosis in different damaged and/or diseased organs. However, the anti‐fibrotic potential of this treatment needs to be elucidated and the cellular and molecular targets of the laser clarified. Here, we investigated the effects of a low intensity 635 ± 5 nm diode laser irradiation on fibroblast–myofibroblast transition, a key event in the onset of fibrosis, and elucidated some of the underlying molecular mechanisms. MATERIALS AND METHODS: NIH/3T3 fibroblasts were cultured in a low serum medium in the presence of transforming growth factor (TGF)‐β1 and irradiated with a 635 ± 5 nm diode laser (continuous wave, 89 mW, 0.3 J/cm 2 ). Fibroblast–myofibroblast differentiation was assayed by morphological, biochemical, and electrophysiological approaches. Expression of matrix metalloproteinase (MMP)‐2 and MMP‐9 and of Tissue inhibitor of MMPs, namely TIMP‐1 and TIMP‐2, after laser exposure was also evaluated by confocal immunofluorescence analyses. Moreover, the effect of the diode laser on transient receptor potential canonical channel (TRPC) 1/stretch‐activated channel (SAC) expression and activity and on TGF‐β1/Smad3 signaling was investigated. RESULTS: Diode laser treatment inhibited TGF‐β1‐induced fibroblast–myofibroblast transition as judged by reduction of stress fibers formation, α‐smooth muscle actin (sma) and type‐1 collagen expression and by changes in electrophysiological properties such as resting membrane potential, cell capacitance and inwardly rectifying K + currents. In addition, the irradiation up‐regulated the expression of MMP‐2 and MMP‐9 and downregulated that of TIMP‐1 and TIMP‐2 in TGF‐β1‐treated cells. This laser effect was shown to involve TRPC1/SAC channel functionality. Finally, diode laser stimulation and TRPC1 functionality negatively affected fibroblast–myofibroblast transition by interfering with TGF‐β1 signaling, namely reducing the expression of Smad3, the TGF‐β1 downstream signaling molecule. CONCLUSION: Low intensity irradiation with 635 ± 5 nm diode laser inhibited TGF‐β1/Smad3‐mediated fibroblast–myofibroblast transition and this effect involved the modulation of TRPC1 ion channels. These data contribute to support the potential anti‐fibrotic effect of LLLT and may offer further informations for considering this therapy as a promising therapeutic tool for the treatment of tissue fibrosis. Lasers Surg. Med. 48:318–332, 2016. © 2015 Wiley Periodicals, Inc.